Idiopathic Infected Hydrocele in a Toddler: A Case Report with Review - Jayesh Sagar; Suhas Kumar; D. Mondal; D.K. Shah (The Scientific World Journal)
Idiopathic infected hydrocele in infants is a rare, but well-documented, entity in English literature; however, occurrence of such a condition in a toddler is not yet documented. Here we report the case of an idiopathic infected hydrocele in a toddler for the first time in English literature. We also discuss a review of literature and demonstrate management of infected hydrocele by antibiotics without any surgical intervention, also for the first time in English literature.